(untitled) (London, 2002)
This book derives from a training course run by ITC for professionals and managers in the environmental sciences, detailing the applications of remote sensing and GIS for environmental monitoring, modelling and assessment. It sets out current research results and provides operational methods for environmental mapping and monitoring.
Keywords: Khoa học môi trường,Environmental sciences; Mô hình toán học,Mathematical models